Sistem Perpajakan antara Regulasi dan Realitas Lapangan - Nisrina, Ulfah Laila (Jurnal Ilmiah Manajemen & Kewirausahaan, 2025)
This study examines the taxation system by exploring the tension between formal regulations and their implementation in real-world practice. While tax regulations are normatively designed to ensure legal certainty and compliance, their application in the field often encounters diverse social and administrative realities. Using a qualitative approach within an interpretive paradigm, this study investigates how tax regulations are understood, interpreted, and enacted by taxpayers in their everyday experiences. Data were collected through in-depth interviews with purposively selected informants who have direct experience with tax compliance, complemented by an analysis of relevant regulatory documents. The findings reveal a noticeable gap between regulatory intentions and practical implementation, as taxpayers’ compliance tends to be administrative and pragmatic rather than grounded in substantive understanding. Moreover, perceptions of fairness, institutional trust, and the quality of interaction with the tax system significantly influence how regulations are received and practiced. This study concludes that challenges in tax compliance cannot be attributed solely to individual taxpayer behavior, but reflect structural and contextual issues within the taxation system. Therefore, improving tax compliance requires approaches that go beyond formal regulation and enforcement, toward more context-sensitive and socially grounded policy implementation.